Analisis Dan Implementasi Honeypot Dalam Mendeteksi Serangan Distributed Denial-Of-Services (DDOS) Pada Jaringan Wireless - Suartana, IMade; Indriyani, Tutuk; Mardiyanto, Bagus (INTEGER: Journal of Information Technology, 2016)
The development of network technology, especially networking security system, demands the security system to evolve. Honeyd is honeypot with low interaction type which has smaller risk than high interaction type. It is because the interaction to honeypot does not directly engage with the real system. In this research, honeyd is integrated with iptables implemented to local network by trying several attacks, such as scanning host, DoS, and Ddos. From the result of honeyd log, the gained information data is processed with honeyd-viz and is expected to become an inputand solution to decide the security policy in network and make the system safer. The experiment showed that honeyd was able to detect the attack by Netscan android by doing scanning host in network. In Ddos attack experiment using Loic, average cpu load before the attack was 15.25%, while after the attack cpu load was 45.98%, and after attack deflection the cpu load was 30.83%.Â